2011
DOI: 10.1103/physrevlett.106.170401
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg-Induced Solitons: Three-Dimensional Self-Trapping of Matter Waves

Abstract: We propose a scheme for the creation of stable three-dimensional bright solitons in Bose-Einstein condensates, i.e., the matter-wave analog of so-called spatiotemporal "light bullets." Off-resonant dressing to Rydberg nD states is shown to provide nonlocal attractive interactions, leading to self-trapping of mesoscopic atomic clouds by a collective excitation of a Rydberg atom pair. We present detailed potential calculations and demonstrate the existence of stable solitons under realistic experimental conditio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
127
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 26 publications
0
127
0
1
Order By: Relevance
“…Quantum degeneracy was recently achieved for strontium atoms [54,55,56]. In contrast to alkali condensates, here Rydberg dressing using the Sr(5sns) states could be used to realize attractive effective ground state atom interactions, which, for example, may permit the creation of three-dimensional bright solitons [57].…”
Section: Discussionmentioning
confidence: 99%
“…Quantum degeneracy was recently achieved for strontium atoms [54,55,56]. In contrast to alkali condensates, here Rydberg dressing using the Sr(5sns) states could be used to realize attractive effective ground state atom interactions, which, for example, may permit the creation of three-dimensional bright solitons [57].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of an axisymmetric nonlocal dipolar interaction [14] a 2D BEC soliton can be generated in a 1D harmonic [11] or a 1D optical-lattice [12] trap. Maucher et al [15] suggested that for Rydberg atoms, offresonant dressing to Rydberg nD states can provide a nonlocal long-range attraction which can form a 3D matter-wave droplet. In this Letter we demonstrate that a tiny repulsive three-body interaction can avoid collapse and form a stable self-bound dipolar droplet in 3D [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the blockade effect for on-resonant excitations [13][14][15][16], one can also apply a far-detuned weak field (see Fig1 (a)) to generate an effective Rydberg-dressed interaction (RDI), which replaces the short-ranged Lennard-Jones potential by a soft core with finite interaction range (see in Fig1(b)) [17][18][19]. Theoretical calculations show that a repulsive RDI in a Bose gas may lead to a supersolid droplet phase [18][19][20][21][22], while an attractive RDI induces a 3D bright soliton [23]. For a Rydberg Fermi gas, some topological phases are also predicted for an attractive [24] or repulsive interaction in a optical lattice near half-filling [25].…”
mentioning
confidence: 99%